Studying the Human Health and Ecological Impacts of the Deepwater Horizon Oil Spill Disaster (Part 2): Introduction to This Special Issue of New Solutions. (February 2019) - Croisant, Sharon; Sullivan, John
This introduction to the special issue continues an examination of the Gulf Coast Health Alliance: Health Risks Related to the Macondo Spill (GC-HARMS) project that began in New Solutions 28:3. GC-HARMS was part of a National Institute of Environmental Health Sciences-funded Gulf-wide consortium that created regional community-university research partnerships addressing health impacts from the oil spill exposures. Findings from this program enhanced regional preparedness and reinforced existing disaster-response networks. This special issue of New Solutions includes an article exploring the outcomes and implications of using a community-based participatory research—citizen science approach in implementing the project's exposure assessment/population health study and another article that describes analytic processes used to characterize toxicity of petrogenic Polycyclic Aromatic Hydrocarbons which provided data used to develop the project's risk message. Finally, this issue includes three Movement Voices interviews from individuals and nonprofits that served as GC-HARMS community hubs during the project.